The end of poverty : economic possibilities for our time - Sachs, Jeffrey (New York : Penguin Books, 2006)
The author shares what he has learned about global poverty through visits to more than one hundred countries, and presents his plan for ending extreme poverty around the world by the year 2025.
Includes bibliographical references (p. [369]-384) and index.
Booklist.
Library Journal Starred.
Pub Weekly.
Booklist, February 2005.
Choice, July 2005.
Keywords: Economic assistance -- Developing countries; Poverty -- Developing countries; Economic policy -- Developing countries; Foreign aid -- Developing countries; Poverty -- Developing countries; Developing countries -- Economic conditions; Developing countries -- Economic policy; Developing countries -- Economic conditions